2018
DOI: 10.1088/1361-6633/aa9966
|View full text |Cite
|
Sign up to set email alerts
|

Remotely controlled fusion of selected vesicles and living cells: a key issue review

Abstract: Remote control over fusion of single cells and vesicles has a great potential in biological and chemical research allowing both transfer of genetic material between cells and transfer of molecular content between vesicles. Membrane fusion is a critical process in biology that facilitates molecular transport and mixing of cellular cytoplasms with potential formation of hybrid cells. Cells precisely regulate internal membrane fusions with the aid of specialized fusion complexes that physically provide the energy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 131 publications
(224 reference statements)
0
20
0
Order By: Relevance
“…Initially, we observed the fusion process on negative GUVs trapped into a microfluidic chip, where the external solution could be exchanged almost instantaneously ($400 ms; see Supporting Materials and Methods; Video S1) using a technology developed previously (48,49). Differently from other microfluidic technology for observing membrane fusion events (14,50), here, we trapped single GUVs, and fusion was initiated by operating an integrated valve to controllably add a specific concentration of LUVs (see Supporting Materials and Methods for details). Our results obtained on chip suggest that fusion is fast, as shown in Fig.…”
Section: Real-time Observation Of Guv-luv Interaction: Membrane Fusiomentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, we observed the fusion process on negative GUVs trapped into a microfluidic chip, where the external solution could be exchanged almost instantaneously ($400 ms; see Supporting Materials and Methods; Video S1) using a technology developed previously (48,49). Differently from other microfluidic technology for observing membrane fusion events (14,50), here, we trapped single GUVs, and fusion was initiated by operating an integrated valve to controllably add a specific concentration of LUVs (see Supporting Materials and Methods for details). Our results obtained on chip suggest that fusion is fast, as shown in Fig.…”
Section: Real-time Observation Of Guv-luv Interaction: Membrane Fusiomentioning
confidence: 99%
“…For this reason, many in vitro systems have been developed in the last few years (see, e.g., (7)) to unravel the molecular requirements of fusion and, in some cases, its intermediates. In synthetic systems, a number of distinct fusogenic stimuli-such as reconstituted proteins (8,9), electric pulses (10,11), laser irradiation (12), plasmonic and nanoheaters (13,14), fusion peptides (15,16), and polymers (17,18)-can mediate fusion, and it is assumed that most fusion events transit through the same fusion intermediates (except in the case of fusion induced by electromagnetic fields), even though they may differ in dynamics. Methods for detecting fusion and its intermediates usually rely on quenching or dequenching of fluorescent lipids present in the membrane, yielding a change in signal (decrease or increase, respectively) upon fusion (see, e.g., (6,(19)(20)(21)).…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has been used for fusion of cells [47] and membrane vesicles [48]. Both pulsed lasers or continuous wave lasers can be used in combination with plasmonic nanoparticles for disrupting membranes [49][50][51][52]. We envision that this technique will provide a fruitful approach for investigation of plasma membrane repair in the future in particular when combined with predictions from theoretical calculation on the stability of membrane holes decorated with annexins scaffolds.…”
Section: Approaches To Inflict Damage To the Plasma Membranementioning
confidence: 99%
“…17,18 Recently, Bendix and Oddershede et al have reported a number of interesting studies of optically-trapped vesicles, including the selective fusion of lipid vesicles through hot-nanoparticle mediated fusion. 1921 The manipulation of organelles inside cells has also been achieved using optical trapping, opening up interesting possibilities for in situ studies. 22,23…”
Section: Introductionmentioning
confidence: 99%